Psychosocial factors in brain infections research in the last decade: A scoping review - Vasundharaa S Nair; Priya Treesa Thomas; M Netravathi (Wolters Kluwer Medknow Publications, 2022)
Background: Brain infections are serious neurological events that require immediate care, with around 171 districts of 19 states in India reporting cases every year. Along with the biomedical factors, psychosocial factors of health (BPS) are influential in the outcomes of brain infections as well. Materials and Methods: A scoping review was conducted to understand the psychosocial factors explored in brain infections in the last decade. Articles focusing on social, psychological, public health factors, sequelae, and rehabilitation of inflammatory conditions, both pathogenic and autoimmune were covered. The search was conducted using keywords related to brain infections in electronic databases: PubMed, EBSCO, ProQuest, Scopus, and Google Scholar. Prisma-ScR guidelines were used to screen articles and the identified factors were categorized under eight psychosocial factors using Arksey and O'Malley's framework of analysis. Results: From a total of 6012 documents retrieved, 11 articles met the criteria. Global burden associated with brain infections, disability and death, the vulnerable population at risk of developing brain infections, gaps in existing literature, pathways to care, mental health, cognitive difficulty associated with infections and their sequelae were the major psychosocial factors identified. Conclusions: The review focussed to understand the multitude of psychosocial factors causing delay and damage in brain infections in LMIC context. Along with biomedical factors, there exist several psychosocial factors that could potentially influence the outcome of treatment in brain infections. However, only few have been explored, suggesting the need for more studies to inform the care and sustainable interventions at the macro level to improve the outcomes and reduce the burden in brain infections.